EFFECT OF THE OPERATING PRESSURE AND NOZZLE HEIGHT ON DROPLETPROPERTIES USING KNAPSACK SPRAYER - Alheidary, M. H. R. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2018)
A field study was performed in the Agricultural Machines and Equipment Department, Agriculture College, Basrah University, to study the effect of the operating pressure and nozzle height on droplet properties reaching to the target using knapsack sprayer with a maximum capacity of 16l. A nozzle is mounted on the rod of sprayer. Three different operating pressures were tested in this study of 1, 1.7, 2 bar and three different nozzle heights of 50, 70, 90cm. Brilliant Sulpho-Flavinedye was used to measure mean droplet sizes, droplet densities, droplets number, and relative span factor deposited on white card papers. The spray properties were determined after spraying in field and then were analyzed using Image J software. The main results of the study showed asignificant effect of operating pressure and nozzle height on mean of the droplet diameter, droplet volume, droplets number, and relative span factor. Increasing the operating pressure from 1 to 2 bar for the some   nozzle height led to decrease droplet diameter by 31.94 % and decrease in mean droplet volume by165.33%. The results also showed that increasing in nozzle height from 50cm to 90cm led to a decrease in the mean of the droplet size of 25.38% and decrease in  droplets volume that reaching to the target by155.86%. The effect of the nozzle height on the spray droplet properties was more than that of increasing operating pressure.